Expression of minichromosome maintenance protein 2 as a marker for proliferation and prognosis in diffuse large B-cell lymphoma: a tissue microarray and clinico-pathological analysis - Obermann, Ellen C (BioMed Central, 2005)
BACKGROUND: Minichromosome maintenance (MCM) proteins are essential for the initiation of DNA replication and have been found to be relevant markers for prognosis in a variety of tumours. The aim of this study was to assess the proliferative activity of diffuse large B-cell lymphoma (DLBCL) in tissue microarray (TMA) using one of the minichromosome maintenance proteins (Mcm2) and to explore its potential value to predict prognosis. METHODS: Immunohistochemistry for Mcm2 was performed on TMAs constructed from 302 cases of DLBCL. A monoclonal mouse antibody was used after heat induced antigen retrieval. Mcm2 expression was scored quantitatively. Positivity for Mcm2 was defined as presence of nuclear expression of Mcm2 in greater than or equal to 40 % of tumour cells. A statistical analysis was carried out of the association of Mcm2 and the clinico-pathological characteristics. RESULTS: Mcm2 expression was clearly evident in the nuclei of proliferating non-neoplastic cells and tumour cells. Positivity for Mcm2 was found in 46% (98/211) of analysable cases. A significant correlation existed between Mcm2 expression and presence of bulky disease (p = 0.003). Poor disease specific survival was observed in patients with DLBCL positive for Mcm2 expression in the univariate analysis (p = 0.0424). CONCLUSION: Mcm2 expression can be used to assess tumour proliferation and may be useful as an additional prognostic marker to refine the prediction of outcome in DLBCL.